3‐D quasi proportional fairness scheduling in relay‐assisted multicell LTE‐A downlink1. Issue 8 (16th June 2016) - Ahmed, Irfan
Abstract: This paper presents a three‐dimensional (3‐D: space‐time‐frequency) quasi proportional fairness (QPF)‐based radio resource allocation and interference coordination scheme in multicell long‐term evolution‐advanced downlink. We formulate the resource allocation and interference coordination problem as a QPF‐based utility maximisation problem, wherein, QPF reduces the complexity compared with the conventional proportional fairness. Interference has been minimised through time, frequency and space domain resource allocation. The proposed 3‐D scheme utilises two time slots for intercell interference management, spatial position‐based frequency resource allocation for intracell interference mitigation, and frequency domain orthogonality across user equipment (UE) and relays for inter‐UE and UE‐relays interference management. It has been shown that the relaxed non‐convex primal problem and the dual problem have zero duality gap under the time‐sharing and tolerable interference constraints. The relaxed optimal problem has been solved through the Lagrange dual method. Simulation results show the efficacy of the proposed 3‐D scheme compared with the recently presented three slots time domain interference coordination with round robin and proportional fairness time domain interference coordination schemes. It has been observed that the proposed heuristic 3D with equal power scheme exhibits same performance as the heuristic 3D with water‐filling power allocation and retains the desired optimal level for more than 60 % of the average users' throughput. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The two‐tier or phantom cellular networks are key enabler of next‐generation cellular networks. In this context, we study spectrum and power allocation in three‐dimensional space for the two‐tier network architecture known as relay‐assisted long‐term evolution‐A downlink. We propose three‐dimensional scheme that utilises two time slots for intercell interference management, spatial position‐based frequency resource allocation for intracell interference mitigation, and frequency domain orthogonality across user equipment (UE) and relays for inter‐UE and UE‐relays interference management.